Caudal Epidural Analgesia using Lidocaine alone and in Combination with Tramadol in Dromedary Camels - Omid Azari; Mohammad Mahdi Molaei; Hamid Roshani (Iranian Journal of Veterinary Surgery, 2014)
Objective- This study was performed to investigate the analgesic effects of lidocaine and lidocaine/tramadol combination in epidural anaesthesia in dromedary camels. Design- Experimental Study Animals- Eight healthy immature dromedary camels Methods - The camels were randomly designed in 2 equal groups. In group L: lidocaine 2% (0.22 mg/kg) and in group LT: a combination of lidocaine 2% (0.22 mg/kg) and tramadol (1 mg/kg) were injected into the first inter-coccygeal (Co1–Co2) epidural space. Onset time and duration of caudal analgesia, sedation and ataxia levels were recorded after drug administration. Results- Epidural lidocaine and co-administration of lidocaine and tramadol produced complete analgesia in the tail, anus and perineum. There were no significant differences in onset and duration of caudal analgesia parameters between groups L and LT (p>0.05). Epidural administration of the lidocaine– tramadol combination resulted in mild to moderate sedation, whilst the animals that received epidural lidocaine alone were alert and nervous during the study. Ataxia was observed in all test subjects and was slightly more severe in camels that received the lidocaine–tramadol mixture. Conclusion and Clinical Relevance- It was concluded that epidural administration of lidocaine plus tramadol resulted in sedation and unnoticeable longer caudal analgesia in standing conscious dromedary camels compared with the effect of administering lidocaine alone.